A disposable, roll-to-roll hot-embossed inertial microfluidic device for size-based sorting of microbeads and cells. Issue 10 (6th April 2016) - Wang, Xiao; Liedert, Christina; Liedert, Ralph; Papautsky, Ian
Abstract : We present a low-cost and disposable inertial microfluidic device fabricated using roll-to-roll hot embossing for size-based sorting of microparticles and cells. Abstract : Inertial microfluidics has been a highly active area of research in recent years for high-throughput focusing and sorting of synthetic and biological microparticles. However, existing inertial microfluidic devices always rely on microchannels with high-aspect-ratio geometries (channel width w < channel height h ) and small cross-sections ( w × h < 50 × 100 μm 2 ). Such deep and small structures increase fabrication difficulty and can limit manufacturing by large-scale and high-throughput production approaches such as roll-to-roll (R2R) hot embossing. In this work, we present a novel inertial microfluidic device using only a simple and low-aspect-ratio (LAR) straight microchannel ( w > h ) to achieve size-based sorting of microparticles and cells. The simple LAR geometry of the device enables successful high-throughput fabrication using R2R hot embossing. With optimized flow conditions and channel dimensions, we demonstrate continuous sorting of a mixture of 15 μm and 10 μm diameter microbeads with >97% sorting efficiency using the low-cost and disposable R2R chip. We further demonstrate size-based sorting of bovine white blood cells, demonstrating the ability to process real cellular samples in our R2R chip. We envision that this R2R hot-embossed inertial microfluidic chip will serve as a powerful yet low-cost and disposable tool for size-based sorting of synthetic microparticles in industrial applications or cellular samples in cell biology research and clinical diagnostics.